SUSTAINABLE DEVELOPMENT TOURISM: RESEARCH IN VIETNAM AFTER COVID -19 (Journal of Pharmaceutical Negative Results, 2022)
Tourism has become a leading economic sector in Vietnam, is termed a "smokeless business," and generates substantial money for the government. However, the present complex evolution of the Covid-19 epidemic has had a significant effect on the whole Industry. Tourism models must be bolstered by the variety of Vietnam's ecosystems, wildlife, and cultural heritage. Nonetheless, the complex dynamics of the present Covid-19 outbreak have had a significant influence on Vietnam's whole tourism economy. Many hotels, restaurants, and retail chains in tourist sites become empty as a result of flight bans, travel restrictions, and tourists' dread of the pandemic's effects. This forewarns of a decline in the tourist industry's earnings in numerous nations, including Vietnam. By synthesising statistics, this article evaluates the influence of the Covid-19 pandemic on tourist development in Vietnam and makes some recommendations for the post-Covid-19 sustainable growth of Vietnam's tourism business.